Efforts to Increase Field Land to Plant Rice Production in The Village of Building District Buke Regency in South Konawe - Amaluddin, La Ode; Awaluddin, Muhamad Asri (UNM Geographic Journal, 2018)
This study aims to find out how the community efforts in improving soil fertility to stabilize rice production and inhibiting factors in its management. The benefits of this research are: a) Practical Benefits, The results of the research are expected to provide a material consideration for local governments to pay attention and provide solutions in improving the fertility of land to stabilize rice production b) Theoretical benefits To increase knowledge and experience for writers, especially in field of land resource geography regarding efforts to improve soil fertility to stabilize rice production c) Benefits to Researchers. The benefits for researchers is to increase insight and knowledge of the author on efforts to improve soil fertility to stabilize rice production. This type of research is a descriptive qualitative research. Data collection techniques in this study is to use questionnaires, interviews, documentation and observation. Informants in this study amounted to 40 people and determined at random. In a land management effort to stabilize rice production, the category is quite good with an average of 3.1 where respondents understand well how in land management to stabilize rice production. Understanding of inhibiting factors is in fairly good category with an average of 3.34 indicating that they are well aware of the inhibiting factors in land management efforts to stabilize rice production.